Regulation of nitrogenase gene expression in anaerobic cultures of Anabaena variabilis. - Helber, J T (1988)
Derepression of nitrogenase gene expression was studied at the mRNA and enzyme activity levels in anaerobic cultures of Anabaena variabilis 29413. Cells, previously grown with ammonium chloride, were incubated in the absence of fixed nitrogen compounds under an Ar atmosphere with dichlorophenyldimethyl-urea present to inhibit oxygen evolution. The appearance of nitrogenase mRNA (measured by dot blot hybridization analysis) and nitrogenase activity (measured as acetylene-reducing activity) was followed, and the cells were also observed by phase-contrast microscopy. Nitrogenase mRNA could be detected after 1.5 to 2.0 h of nitrogen starvation; enzyme activity appeared about 1 h later. Although enzyme activity increased for many hours, mRNA levels reached a steady state rapidly. Neither heterocysts nor proheterocysts formed under these conditions; however, the cells were observed to shrink and become chlorotic. When anaerobic, derepressed cultures were exposed to oxygen, nitrogenase mRNA levels decreased very rapidly.